Birthday machine - Ring, Susan; Okabe, Anna; Playhouse Disney (Firm) (New York : Disney Enterprises, 2006)
The Little Einsteins search for the four pieces of the birthday machine so they can throw a great party for Rocket.
Cover title.
On lift-the-flap board pages.
3.1
K-3
Keywords: Birthdays -- Juvenile fiction; Toy and movable books -- Specimens; Birthdays -- Fiction; Toy and movable books; Birthdays -- Fiction; Toy and movable books